Designing Modular Assembly of Electrochemical Flow Microreactor as an Enabling Technology of Electrosynthesis in Laminar Flow. Issue 45 (1st December 2022) - Yata, Ayano; Nakamura, Yuto; Okamoto, Kazuhiro; Shida, Naoki; Atobe, Mahito
Abstract: Flow microreactors are well‐suited for organic electrosynthesis because they provide a large surface area for reactions and enable precise control of the residence time. Here, we developed three novel electrochemical flow microreactors for organic electrosynthesis: undivided, divided, and electrophotochemical reactors. These flow reactors were easily assembled using modules made of solvent‐resistant plastics and feature high interchangeability of each component and the applicability of a reference electrode. We evaluated our reactors on the basis of the redox response of ferrocene and ferrocenemethanol. The results suggested that the reactors maintain laminar flow with both aqueous and nonaqueous electrolytes. We applied these reactors to paired electrosynthesis and electrophotocatalysis, demonstrating the utility of these systems for electrosynthesis in a laminar flow. Abstract : Here, three newly developed microreactors for organic electrosynthesis in laminar flow are reported: undivided, divided, and electrophotochemical reactors. These flow reactors are easy to assemble, compatible with various organic solvents, and adaptable with a reference electrode. Paired electrolysis and electrophotocatalysis in a flow reactor are successfully demonstrated.